Getting Real? The Uneven Burden of Inflation across Households in Turkey - Baez, Javier E.; Inan, Osman Kaan; Nebiler, Metin (World Bank, Washington, DC, 2021)
Inflation is typically measured using aggregate price indices that are based on bundles of goods and services sold or consumed by the “median” agent. In the case of households, in particular, budget shares vary substantially across income and demographic groups. Assessing how inflation behaves at the household level requires understanding how heterogenous changes in consumer prices affect household choices and well-being differently. In recent years, price increases have been particularly high in Turkey, with double-digit inflation starting in 2017 and intensifying in 2018 and 2020 due to exchange rate volatility, macroeconomic instability, and the economic disruption brought about by Covid-19. This paper calculates income-decile price indices to examine the inflation experience across income groups and discusses their implications for household welfare. Households in the first decile allocate nearly 70 percent of their budget to food and housing, twice as much as the corresponding share for the typical household in the upper decile. Inflation measures that consider these heterogeneities in expenditures show a higher burden for the poor in recent inflation episodes driven by rapid increases in food prices (2013, 2015 and 2019). In 2015, for instance, 342,000 additional people would have been deemed poor (an increase of 4.2 percent) had the poverty calculations taken into account the actual inflation experience of poor and vulnerable households. A methodological extension of the World Bank’s upper-middle-income poverty line ($5.50 2011 purchasing power parity) that takes into consideration the inflation experience of the bottom deciles yields higher poverty rates for Turkey every year between 2011 and 2020.